Management Of Health Practice Places That Do Not Have A Permission - Sri Cindrawati Abdullah (Universitas Negeri Gorontalo, 2020)
Abstract: This study aims to determine the actions of the police in tackling unlicensed health practices in Gorontalo Regency.This type of research is a normative-empirical legal research using a statutory approach and a case approach and the data obtained in this study were analyzed qualitatively, namely by collecting data, qualifying then connecting theories related to the problem and drawing conclusions to determine the results. Actions from the police as an effort to overcome health practices that do not have permits are preventive efforts, namely efforts that lead to how the actions of the police before the occurrence of a crime, namely the police coordinate with the local government in order to issue a letter to every existing health center. , not to open a health practice without a permit. Then when it is known that there is a place of practice that does not have a permit, the police will carry out an investigation process in accordance with the provisions of the law or what is called a repressive effort. Actions from the police are more emphasized in terms of taking action to deal with health practices that do not have permits. Because in providing legal firmness and providing a sense of security for legal services, firmness is needed to make efforts or actions from the police to minimize the existence of malpractice victims by going directly in the field in disciplinary efforts for health workers who do not have permits. Actions from the police are more emphasized in terms of taking action to deal with health practices that do not have permits. Because in providing legal firmness and providing a sense of security for legal services, firmness is needed to make efforts or actions from the police to minimize the existence of malpractice victims by going directly in the field in disciplinary efforts for health workers who do not have permits. Actions from the police are more emphasized in terms of taking action to deal with health practices that do not have permits. Because in providing legal firmness and providing a sense of security for legal services, firmness is needed to make efforts or actions from the police to minimize the existence of malpractice victims by going directly in the field in disciplinary efforts for health workers who do not have permits.Keywords: Countermeasures; Permission; Health Practice